Constitutive cleavage of the single-pass transmembrane protein alcadeinα prevents aberrant peripheral retention of Kinesin-1. - Chiaki Maruta; Yuhki Saito; Saori Hata; Naoya Gotoh; Toshiharu Suzuki; Tohru Yamamoto (PLoS ONE, 2012)
Various membrane proteins are shed by proteinases, constitutively and/or when stimulated by external signals. While the physiological significance of external signal-induced cleavages has been intensely investigated, relatively little is known about the function of constitutive cleavages. Alcadeinα (Alcα; also called Calsyntenin-1) is an evolutionarily conserved type I single-pass transmembrane protein that binds to kinesin-1 light chain (KLC) to activate kinesin-1's transport of Alcα-containing vesicles. We found that Alcα was constitutively and efficiently cleaved to liberate its ectodomain into the extracellular space, and that full-length Alcα protein was rarely detected on the cell surface. The secretion efficiency of the ectodomain was unaltered by a mutation that both abolished Alcα's KLC-binding activity and attenuated its peripheral transport, suggesting that Alcα's cleavage occurred, at least partly, en route to the cell surface. We further demonstrated that uncleavable mutant Alcα proteins readily accumulated on the cell surface and induced aberrant peripheral recruitment of KLC1 and kinesin heavy chain. Our observations suggest that Alcα is efficiently processed in part to minimize the inappropriate peripheral retention of kinesin-1. This role might exemplify the functional relevance of the constitutive cleavage of single-pass transmembrane proteins.